1991
DOI: 10.1007/bf01244707
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecificity of the dopamine receptor mediating the growth hormone response to apomorphine in man

Abstract: The stereospecificity of the D-2 receptor mediating the growth hormone (GH) response to apomorphine (Apo) and the D-2 receptor regulating prolactin (PRL) secretion were investigated in 10 normal men by examining the effects of cis-flupenthixol (cis-Fx) and trans-flupenthixol (trans-Fx). cis-Fx (1 mg six hourly times four doses) antagonized the GH response to Apo HCl (0.5 mg sc) and increased basal serum PRL concentrations whereas the trans-isomer showed no effect. These findings (a) provide further evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Both stimulatory and inhibitory dopaminergic effects on the somatotrophic system have been reported. Basal GH secretion in healthy subjects is stimulated by DA (14, 15, 18, 28), dopaminergic agonists (19, 28, 29) and l ‐dopa (21, 22, 30). The stimulatory actions of l ‐dopa appear to persist in patients with IPD (2, 3), although an acquired defect in release of GH following years of l ‐dopa therapy has also been reported (25).…”
Section: Discussionmentioning
confidence: 99%
“…Both stimulatory and inhibitory dopaminergic effects on the somatotrophic system have been reported. Basal GH secretion in healthy subjects is stimulated by DA (14, 15, 18, 28), dopaminergic agonists (19, 28, 29) and l ‐dopa (21, 22, 30). The stimulatory actions of l ‐dopa appear to persist in patients with IPD (2, 3), although an acquired defect in release of GH following years of l ‐dopa therapy has also been reported (25).…”
Section: Discussionmentioning
confidence: 99%
“…During withdrawal, the number increases to above-normal levels (rebound phenomenon; Rommelspacher et al, 1992). Moreover, there is evidence that GH release after dopaminergic stimulation depends upon the interaction of dopamine D2-receptors (Tallo and Malarkey, 1981;Fabbrini et al, 1988;Lal et al, 1991) with G-proteins (Bunzow et al, 1988;Enjalbert et al, 1988;Landis et al, 1989). It has been observed that G-protein levels are reduced during chronic intoxication (Mochly-Rosen et al, 1988;Wand and Levine, 1991;Diehl et al, 1992).…”
Section: Introductionmentioning
confidence: 96%